Kombinasi Herbal Angco (Ziziphus Jujuba) Dan Akupunktur: Inovasi Terapi Nyeri Lutut Lansia - Aditya, Stefanus; Ningrum, Anis Lupita; Rosyida, Muslihatin Khuril (Universitas Pahlawan Tuanku Tambusai, 2025)
Knee pain is a common musculoskeletal complaint, particularly in the elderly. This disorder involves damage or dysfunction to structures such as bones, knee joints, and surrounding soft tissues, including nerves, tendons, ligaments, muscles, and blood vessels. One non-pharmacological approach proven effective in treating knee pain is acupuncture therapy. This therapy plays a role in improving blood circulation, stimulating cartilage matrix repair, reducing joint space narrowing, and helping to gradually relieve pain. This study was conducted from September to April 2025 at the Panti Sasana Tresna Wredha Yayasan Dharma Bakti in Wonogiri Regency. A sample of 32 patients met the inclusion and exclusion criteria. They were then treated with a combination of Angco/Jujube (Ziziphus Jujube) herbal infusion and local acupuncture therapy. This study used a quantitative, quasi-experimental design with a two-group pre- and post-test design. Knee pain severity was measured using the VRS (Verbal Rating Scale). Based on the Mann-Whitney test, a significant value of ρ = 0.035 was obtained. This means that acupuncture therapy combined with Angco/Jujube (Ziziphus Jujube) herbal infusions is effective in reducing knee pain. Based on this study, it was concluded that combination therapy using Angco/Jujube (Ziziphus Jujube) herbal infusions is effective in reducing knee pain at the Panti Sasana Tresna Wredha Yayasan Dharma Bakti Wonogiri Regency.